THE EFFECTS OF EXPERIMENTAL SPLENIC AUTOTRANSPLANTATION AND IMIPENEM-CILASTATIN TREATMENT IN POSTSPLENECTOMY PSEUDOMONAS-AERUGINOSA SEPSIS - (:unkn) unknown (SPRINGER VERLAG, 1995)
Male Wistar albino rats were allocated to three groups - sham operated (n: 10), splenectomized (n: 20) and splenic autotransplanted (n: 10). Twelve weeks after operation, all were challenged with 1.8 x 10(8) cfu/ml Pseudomonas aeruginosa intranasally. Half of the splenectomized rats received imipenem-cilastatin after 2 h of bacterial challenge. Mortality was then observed for the next 12 days. All animals were autopsied and liver, kidney, spleen and lung specimens were processed for microbiological culture and histopathological examination. In 80% of autotransplanted rats, splenic tissue regeneration was histopathologically verified. Hemoglobin oxidation of erythrocytes increased in splenectomized rats and remained close to control levels in the autotransplanted group. No significant difference was detected between IgM levels of splenectomized and autotransplanted groups. Mortality rates were the same for all groups, except that splenectomized animals given antimicrobial therapy had increased survival rates. In conclusion, it is likely that the spleen has no role in protection against pulmonary sepsis and that only appropriate antimicrobial therapy can protect the splenectomized host from Pseudomonas sepsis.
Keywords: POSTSPLENECTOMY SEPSIS; PSEUDOMONAS AERUGINOSA; SPLENECTOMY; SPLENIC AUTOTRANSPLANTATION; HEMOGLOBIN OXIDATION; SPLENECTOMY; SPLEEN; PRESERVATION; PROTECTION; RATS